Pengaruh Metode Hypnoteaching terhadap Hasil Belajar IPS Siswa Kelas IV UPT SD Negeri 181 Inpres Pattopakang Kabupaten Takalar - Arda Gina Cahyani; Nursalam Nursalam; Ulfayani Hakim (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This research aims to describe and determine the influence of the Hypnoteaching Method on the Social Sciences Learning Outcomes of Class IV Students at UPT SD Negeri 181 Inpres Pattopakang, Takalar Regency. This research uses a Quantitative Experimental research method. The population in this study were all UPT students at SD Negeri 181 Inpres Pattopakang, Takalar Regency. The sampling technique used in this research is the Purposive Sampling technique, the sample in this research is all 34 class IV students. The instruments used in this research were observation of learning outcomes tests and documentation. The data analysis technique used was descriptive statistics and inferential statistics. The results of the research were based on descriptive analysis using SPSS version 26 regarding fourth grade students at UPT SD Negeri 181 Inpres Pattopakang, Takalar Regency. The average value of learning outcomes before applying the hypnoteaching method was 46.32 and after applying it. increased to 83.68. Based on inferential analysis with the help of SPSS version 26 in the normality test using the Kolmogrov-Smirnov test and it can be said that the data meets the assumption of normality because the significance value is >0.05 and in the independent sample t-test hypothesis test the value obtained sig (2-tailed) < 0.05 in the sense that H0 is rejected and H1 is accepted. From the results of the Normalized Gain Score (N-Gain) test, a value of 0.69 was obtained in the medium category and for the N-Gain percent, a value of 69.60 was obtained with a fairly effective classification. So it can be said that there is an influence of the hypnoteaching method on the social studies learning outcomes of class IV UPT SD students. Negeri 181 Pattopakang Presidential Instruction, Takalar Regency.